Use of Encapsulation Technology in Meat Industry - Ali SOYUÇOK; Birol KILIÇ; Gülden BAŞYİĞİT KILIÇ (Mehmet Akif Ersoy Üniversitesi Fen Bilimleri Enstitüsü, 2019)
Encapsulation technology used in food science area is the process of coating food components, flavors, sweeteners, colorants, vitamins, minerals, enzymes and microorganisms with different techniques using a coating material. Studies in this area started with the addition of encapsulated vitamins to infant formula and accelerated by the use of encapsulated fish oils in different food matrices. Due to the differences in technological, geographic and microbiological conditions, there are always problems in producing meat products with the same quality and reliability. In addition, inhibition of lactic acid bacteria in heat-treated products causes some quality defects such as inadequate taste and aroma formation. Thus, using encapsulation technology in fermentation process increase the efficiency and specific product characteristics development in meat products provided. Studies have shown that heat-treated meat products produced by using encapsulated cultures provided desired taste and flavor, and stable bacteria count during processing and storage of production.